SARS COV-2 and Inflammation: Its Impact on the Cardiovascular System - Qadir, Muneeb; Bhagat, Saumya; Quasimi, Huma; Ali, Intzar; Khan, Afreen; Ansari, Mairaj Ahmed; Alam, Iqbal (Cardiology and Cardiovascular Medicine, 2022)
The novel corona virus is identified as a positive–sense single–stranded RNA virus and member of the coronavirus family. The virus is thought to have originated from Wuhan, China, and acquired the ability of human–to–human transmission. Although most patients with SARS–CoV–2 (previously known as “2019 novel coronavirus”) manifest fever and respiratory tract symptoms. SARS–CoV–2 infection may also involve other organs/systems and present with extra–respiratory manifestations including cardiac, gastrointestinal, hepatic, renal, neurological, olfactory, gustatory, ocular, cutaneous and hematological symptoms. The severe risk factors are commonly detected in elder patients and with medical comorbidities like cancer, hypertension and diabetes. Since the outbreak and rapid spread of SARS–CoV–2, it has been evident that disease prognosis has largely been influenced by multi–organ involvement. Comorbidities such as cardiovascular diseases have been the most common risk factors for severity and mortality. The involvement of different organs of the body is explained based on the presence of ACE–2 (angiotensin–converting enzyme 2) in different tissues and cells. Several extra–respiratory manifestations, such as cardiac involvement, acute kidney injury, coagulation disorders, and thrombotic complications, could be associated with a poor prognosis. This review provides a comprehensive presentation of the pathophysiological effects of SARS–CoV–2 infection on different organs of the body such as CVS (cardiovascular system), CNS (central nervous system), GIT (gastrointestinal tract), Skin, Renal, and Blood.